Segmental basal cell naevus syndrome caused by an activating mutation in smoothened. (20th June 2016) - Khamaysi, Z.; Bochner, R.; Indelman, M.; Magal, L.; Avitan‐Hersh, E.; Sarig, O.; Sprecher, E.; Bergman, R.
Summary: Aberrant sonic hedgehog signalling, mostly due to PTCH1 mutations, has been shown to play a central role in the pathogenesis of basal cell carcinoma (BCC), as well as in basal cell naevus syndrome (BCNS). Mutations in smoothened ( SMO ) encoding a receptor for sonic hedgehog have been reported in sporadic BCCs but not in BCNS. We report a case with multiple BCCs, pits and comedones in a segmental distribution over the upper part of the body, along with other findings compatible with BCNS. Histopathologically, there were different types of BCC. A heterozygous mutation (c.1234C>T, p.L412F) in SMO was detected in three BCCs but not in peripheral blood lymphocytes or the uninvolved skin. These were compatible with the type 1 mosaic form of BCNS. The p.L412F mutation was found experimentally to result in increased SMO transactivating activity, and the patient responded to vismodegib therapy. Activating mutations in SMO may cause BCNS. The identification of a gain‐of‐function mutation in SMO causing a type 1 mosaic form of BCNS further expands our understanding of the pathogenesis of BCC, with implications for the treatment of these tumours, whether sporadic or inherited. Abstract : What's already known about this topic? Mutations in smoothened ( SMO ) have been previously reported in acquired basal cell carcinomas but not in basal cell naevus syndrome (BCNS). What does this study add? A gain‐of‐function mutation in SMO was demonstrated in the type 1 mosaic form of BCNS, which further expands the understanding of this syndrome. Linked Comment: Ahn. Br J Dermatol 2016; 175 :21–22